Elegy for April : a novel - Black, Benjamin, 1945- (New York : Henry Holt and Co., 2010)
Quirke, a Dublin pathologist, is determined to find his daughter's best friend, a well-connected young doctor. Sober again after intensive treatment for alcoholism, Quirke enlists his old sparring partner, Detective Inspector Hackett, in the search for the missing young woman. Set in Dublin, circa 1950.
Keywords: Pathologists -- Fiction; Dublin (Ireland) -- Fiction; Psychological fiction; Mystery fiction